Pemberdayaan Kelompok Wanita Tani (KWT) Melalui Pembagian Benih Sayuran Dalam Rangka Mendukung Ketahanan Pangan Keluarga - Umi Nur Solikah; Mohamad Ihsan; Arifah Husna; Rehino Yanu Seto; Chanda Firdaus; Mufida Diah Lestari (LP3M INSTITUT KH YAZID KARIMULLAH, 2023)
Vegetables play an important role in human life. Because vegetables are a source of vitamins and minerals that are good for health. The large number of cases of stunting in children today is caused by, among other things, a lack of nutritious food, including vegetables. In general, the people of Colomadu District, Karanganyar Regency do not fully utilize their home gardens. By distributing vegetable seeds to women farmer groups (KWT) in Colomadu District, the Women Farmer Groups can optimize their yard land so as to support the Framework for Supporting Family Food Security. Steps taken in the community service activity